2015
DOI: 10.1002/eji.201545591
|View full text |Cite
|
Sign up to set email alerts
|

Fonsecaea pedrosoi‐induced Th17‐cell differentiation in mice is fostered by Dectin‐2 and suppressed by Mincle recognition

Abstract: Chromoblastomycosis is a chronic skin infection caused by the pigmented saprophytic mould Fonsecaea pedrosoi. Chronicity of infection can be broken by a coordinated innate recognition of the spores by pattern recognition receptors. While Mincle signaling via theKeywords: Chromoblastomycosis r C-type lectin r Fungi r Dectin-2 r Mincle r T-cell differentiation r Th17 cell Additional supporting information may be found in the online version of this article at the publisher's web-site IntroductionChromoblastomycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 41 publications
(74 reference statements)
2
60
0
3
Order By: Relevance
“…Several potential virulence factors are probably involved in this disease, including modifications of the cell surface, hydrophobicity, remodeling of the fungal cell wall, secretion of proteolytic and hydrolytic enzymes, adhesion molecules, incorporation of aromatic hydrocarbons, assembly of siderophores, and especially the presence of melanin. Most of the virulence and pathogenic factors observed in chromoblastomycotic infections are largely similar to those for infections by other pathogenic fungi (160)(161)(162)(163). Factors that are significant for the pathogenicity of CBM are melanin, muriform cells, cell adhesion, and hydrophobicity.…”
Section: Pathogenesis and Host Defensementioning
confidence: 89%
See 1 more Smart Citation
“…Several potential virulence factors are probably involved in this disease, including modifications of the cell surface, hydrophobicity, remodeling of the fungal cell wall, secretion of proteolytic and hydrolytic enzymes, adhesion molecules, incorporation of aromatic hydrocarbons, assembly of siderophores, and especially the presence of melanin. Most of the virulence and pathogenic factors observed in chromoblastomycotic infections are largely similar to those for infections by other pathogenic fungi (160)(161)(162)(163). Factors that are significant for the pathogenicity of CBM are melanin, muriform cells, cell adhesion, and hydrophobicity.…”
Section: Pathogenesis and Host Defensementioning
confidence: 89%
“…Recent studies have shown that impaired fungal clearance in CBM infections is due mainly to the enhanced virulence and pathogenicity of the etiological agents (159)(160)(161). Several potential virulence factors are probably involved in this disease, including modifications of the cell surface, hydrophobicity, remodeling of the fungal cell wall, secretion of proteolytic and hydrolytic enzymes, adhesion molecules, incorporation of aromatic hydrocarbons, assembly of siderophores, and especially the presence of melanin.…”
Section: Pathogenesis and Host Defensementioning
confidence: 99%
“…MCL also has been shown to play a protective role in innate host defense against Gram-negative pneumonia (22). Aside from studies with C. albicans and Fonsecaea pedrosoi (13,23), the role of MCL in antifungal immunity remains poorly defined. Interestingly, MCL was shown to form a heterodimer with Dectin-2 to synergistically induce NF-B in response to C. albicans hyphae (24).…”
mentioning
confidence: 99%
“…In vivo, dectin-2 has been shown to exert a protective role against C. albicans, C. glabrata , and T. rubrum infections [31] and, together with MCL, they have been suggested to promote Th17 responses to Fonsecaea pedrosoi and Blastomyces dermatitidis, respectively [32, 33], while Mincle can antagonize these responses [32]. Mice deficient in MCL show impaired vaccine resistance against B. dermatitidis infections, and this lack of resistance was associated with a reduced recruitment of Th17 cells to the lung upon recall following experimental challenge [33].…”
Section: The Dectin-2 Clustermentioning
confidence: 99%